English Writing Skill of Bengali Medium Students: Comparison between First-Generation Learners (FGL) and non-First-Generation Learner (NFGL) - Subir Sen (LinguaScopes: International Journal of Language Education, 2026)
English writing skill is essential for the students of India in modern society. This skill is essential for the students to become a global learner. Although, this skill is taught from primary stages, secondary level is very crucial for the development of the writing skill especially in English. FGLs are very much neglected to achieve the English writing skill by several means in West Bengal, India. Objectives for this study were to compare attitude, connect activities of different components and achievements between FGL and NFGL students. Five null hypotheses are framed to compare achievements between FGL and NFGL students. A mixed method approach is followed to analyze results. 1200 secondary level students are considered as a sample using stratified random sampling method. All students at first interviewed with the help of 6 questions and after that an essay type test on English writing skill was administered. A network analysis was performed based on the results of written test scores for different components. Performance of writing skill between FGL and NFGL for five different components of English writing skill was done using t-tests. Several issues were found regarding English writing skill. It was found that NFGL secured better position in enjoyment, interest, confidence, student-teacher interaction, use of internet and regular practice. In every component of English writing skill, NFGL students performed significantly better than FGL students. Supervision, proper feedback and guidance is recommended for the improvement of English writing skill for a FGL students.